Transmission of coconut cadang-cadang viroid oil palm variants to oil palm tissue culture plantlets / Hendry Joseph… [et al.] - Joseph, Hendry; Vandamalai, Gandesan; Abdullah, Siti Nor Akmar; Lau, Wei Hong; Randles, John W.; Abu Seman, Idris (Universiti Teknologi MARA, Sabah, 2017)
This study was conducted to transmit Coconut cadang-cadang viroid (CCCVd) variants to oil palm tissue culture plantlets. The source of inoculum was extracted by using the polyethylene glycol (PEG) extraction method from the leaflets of an oil palm with the orange spotting (OS) symptom and which has tested positive as a CCCVd oil palm variant. The concentration of leaf extract was adjusted to 20μg/ml and inoculated into 1 to 3-month-old plantlets with a high pressure injector. Six months after inoculation, the orange spotting symptom was observed on the leaflet of the plantlet. When subjected to dot blot assay, the sample hybridised with the CCCVd246 full-length complementary probe, indicating the presence of CCCVd-like RNAs in the inoculated plantlet. This suggests that the CCCVd oil palm variants have been successfully transmitted into the host. This study has demonstrated the effectiveness of using a high pressure injector in transmitting CCCVd oil palm variants and showed the potential of using oil palm tissue culture plantlet in pathogenicity studies due to benefits in terms of economies of time, space and labour.